Estimates of age specific death rates in people with diabetes and associated multimorbidity using Australian administrative pharmaceutical data - Purkiss, Shaun Francis; Keegel, Tessa; Vally, Hassan; Wollersheim, Dennis (International Journal of Population Data Science, 2021)
Introduction Estimating the mortality risk of persons with diabetes can be challenging. Associated conditions such as cardiovascular disease can become the primary cause of mortality and the underlying contribution of diabetes not recorded. Alternative methods to assess mortality risk in people with diabetes would be useful. Objective To evaluate an Australian pharmaceutical database to identify multi-morbidity cohorts associated with diabetes and determine mortality rates in these groups using prescription exchange cessation as a proxy event for death. Methods Australian Pharmaceutical Benefits Scheme data covering the period 2003–14 were used. Persons with diabetes, cardiovascular diseases and dyslipidemia were identified using Anatomic Therapeutic Chemical codes allocated to their recorded dispensed treatments. People with combinations of these conditions were followed and the last recorded prescription exchange used as a proxy event for mortality. Age and gender specific mortality rates and mortality rate ratios for the multi-morbidity cohorts were then calculated from the number of deaths occurring within 10 years. Results 346,201 individuals were identified as taking treatments for diabetes, dyslipidemia and cardiovascular conditions in 2004, 86,165 deaths occurred within 10 years of follow up. Overall crude mortality was 26.2/1,000 person years. Age specific mortality rates and rate ratios were calculated for various multi-morbidity groupings. Statin treatments improved the mortality rates associated with diabetes and cardiovascular disease in persons age >54 (Log–Rank <.001). Conclusions Administrative pharmaceutical data can be used to identify persons with diabetes and associated multi-morbidities. Proxy mortality events defined by the cessation of treatment can generate mortality rates, providing an alternative perspective for the assessment of mortality risk.